2022
DOI: 10.1093/biolre/ioac147
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota: a double-edged sword in endometriosis

Abstract: Endometriosis that afflicts 1 in 10 women of reproductive age is characterized by growth of endometrial tissue in the extra-uterine sites and encompasses metabolic-, immunologic- and endocrine-disruption. Importantly, several comorbidities are associated with endometriosis, especially autoimmune disorders such as inflammatory bowel disease. Primarily thought of as a condition arising from retrograde menstruation, emerging evidence uncovered a functional link between the gut microbiota and endometriosis. Specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 190 publications
0
16
0
Order By: Relevance
“…Therefore, endometriosis-associated pain may be affected by regulation of microglia and astrocytes via the dysbiotic gut-brain axis ( 65 ). Severe pain and infertility associated with endometriosis have been reported to be associated with decreased cervical microbial diversity and abundance ( 66 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, endometriosis-associated pain may be affected by regulation of microglia and astrocytes via the dysbiotic gut-brain axis ( 65 ). Severe pain and infertility associated with endometriosis have been reported to be associated with decreased cervical microbial diversity and abundance ( 66 ).…”
Section: Resultsmentioning
confidence: 99%
“…Animal studies have demonstrated that gut microbiome plays a crucial pro-inflammatory role in the progression of endometriosis and results in higher levels of IL-1β, TNF-α, IL-6, and TGF-β1 and an increase in macrophages at the lesion site [ 26 ]. Short-chain fatty acids, like acetate, propionate, and n-butyrate, are bioactive metabolites produced through the processing of indigestible nutrients by the gut microbiome [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…While there is evidence of a dysregulated gut or reproductive tract microbiome in women with endometriosis, there is little consensus regarding the particular microbiota that may lead to endometriotic lesion growth 101 . Additionally, some bacteria promote endometriosis and others potentially protect against it highlighting the need for further investigations into this area 102 …”
Section: New Concepts On the Etiology Of Endometriosismentioning
confidence: 99%
“… 101 Additionally, some bacteria promote endometriosis and others potentially protect against it highlighting the need for further investigations into this area. 102 …”
Section: New Concepts On the Etiology Of Endometriosismentioning
confidence: 99%